2022
DOI: 10.3390/antibiotics11030373
|View full text |Cite
|
Sign up to set email alerts
|

Meropenem/Vaborbactam Plus Aztreonam as a Possible Treatment Strategy for Bloodstream Infections Caused by Ceftazidime/Avibactam-Resistant Klebsiella pneumoniae: A Retrospective Case Series and Literature Review

Abstract: Objectives: The aim of this study was to describe our experience of a combination treatment including meropenem/vaborbactam (M/V) plus aztreonam (ATM) for bloodstream infections (BSIs) due to ceftazidime/avibactam-resistant Klebsiella pneumoniae (CAZ/AVI-R-Kp), for which gene typing was not available at the time the blood culture (BC) results were obtained. Methods: Between 20 July and 22 August 2021, in our hospital laboratory, the molecular test for carbapenemase gene typing was not available. All Gram-negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…Alternatively, when we have evidence for a CRE infection, but we do not know the resistance phenotype, we can initially treat with a novel beta-lactam/beta-lactamase inhibitor plus aztreonam. When the susceptibility test results become available, we can de-escalate treatment accordingly [ 171 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, when we have evidence for a CRE infection, but we do not know the resistance phenotype, we can initially treat with a novel beta-lactam/beta-lactamase inhibitor plus aztreonam. When the susceptibility test results become available, we can de-escalate treatment accordingly [ 171 ].…”
Section: Discussionmentioning
confidence: 99%
“…Newer drugs such as ceftazidime/avibactam have shown good clinical outcomes and better survival outcomes when compared with colistin-based combinations for CRE infections [ 5 , 36 ]. Additionally, meropenem/vaborbactam, which has recently been demonstrated to be a potential therapeutic strategy against ceftazidime/avibactam-resistant Klebsiella pneumoniae when combined with ATM [ 37 ], showed better clinical cure rates compared to colistin- or tigecycline-based combinations in treating patients with CRE infections [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study showed similar efficacy between MEV and CZA for the treatment of KPC-producing Enterobacterales -related infections [ 49 ]. Meropenem/vaborbactam may be effective against KPC-producing Enterobacterales resistant to CZA [ 50 , 51 , 52 ].…”
Section: What Is To Be Learnt From the Published Studies?mentioning
confidence: 99%